A simulation study on performance characteristics of simulated biogas engine with high compression ratio - Quoc Khanh Nguyen,; Thanh Cong Huynh,; Thanh Tung Nguyen, (Journal of Technical Education Science, 2018)
This paper presents a simulation study on engine performance characteristics of a high compression ratio biogas engine for high efficiency and low emission. A small diesel-type engine with a power of 14 horse power (HP) was modelled for simulating analysis with help of AVL Boost (a thermodynamic analyzing tool). Biogas includes CH4 and CO2 mainly. The ratio of CH4-CO2 was changed from 50%-50% (in volume) to 80%-20% with a step of 5%-5%. Original engine compression ratio is 18:1. Engine operating conditions were set up at: full-load, spark timing of 7 degrees before top dead center (bTDC), and lambda λ=1. In obtained results, in comparison of diesel operation, maximum engine output power was reduced but engine exhaust emission (CO, NOx) was improved for operation with biogas that is significantly result in term of ecological protection. For example, in comparison of diesel operation, biogas operation could conduct a reduction of about 7.7% and 63% for ratio of 80%-20% and 50%-50%, respectively.